Peningkatan Kreativitas Anak Usia Dini melalui Permainan sebagai Edukasi Media Belajar Kreatif di PAUD Kabupaten Karawang - Ditha Prasanti; Sarah Aisha (Jurnal Gema Ngabdi, 2023)
Kindergarten (PAUD) as a second learning vehicle after the family environment for early childhood, gives a distinct impression for those who experience it. As a place to play while learning that is full of educational values, it should provide varied learning. Especially in the current digital era, early childhood learning media must also be developed. This is the reason we carry out Community Service (PkM) activities targeting early childhood children in an early childhood education center located in Ciparagejaya village, Karawang district. Its location close to the coast, becomes a learning vehicle for the people who are there. Therefore, we also carried out PkM activities with the title "Improving Early Childhood Creativity through Games as Creative Learning Media Education in PAUD Ciparagejaya Village, Karawang Regency". The purpose of implementing PkM is to increase the creativity of early childhood in the PAUD environment through creative learning media education. The PkM method used is the roleplay method and the participatory method, where children are directly involved in learning activities through games as a form of creative learning media education. The results obtained indicate the active participation of children in the learning process, train children's creativity through creative learning media stimuli, and instill moral values in the form of honesty, self-confidence, as well as perseverance and enthusiasm for learning.